Cancer Risk and Barbeque Trend in Indonesia: Efforts to Reduce Cancer Burden - Nathania, Maggie; Octovia, Lily Indriani (Majalah Kedokteran Indonesia, 2019)
In the last decades, concerns have been raised about the shift in the dietary patterns towards a high energy dense diet, mainly higher red meat consumption. The amount of meat consumption per person has almost doubled between 1961 and 2013 from 23 kilograms to 43 kilograms per year worldwide.